HOST BIOLOGY INTERACTIONS OF EPILACHNA VIGINTIOCTOPUNCTATA FABR - JAMWAL, VISHAV VIR SINGH; AHMAD , HAFEEZ; SHARMA, DEVINDER (The Bioscan, 2013)
The Studies conducted during 2008 and 2009 at Sher-e-Kashmir University of Agricultural Sciences and Technology, Chatha, Jammu revealed that 16 cultivated and 3 wild plants growing in the vicinity of the brinjal and bitter gourd crop fields offer shelter to the pest and maintain its population throughout the year. Effect of eight major host plants on all the biological parameters of the test insect included in the study revealed that grub and pupal development, survival, longevity and fecundity of Epilachna vigintioctopunctata (F.) (Coleoptera: Coccinellidae) adults on given host plants under laboratory conditions (29±1ºC, 60-70% RH) differ significantly. In a choice test E. vigintioctopunctata females oviposited most on Solanum nigrum (286.80 ± 19.86 eggs), least on Luffa acutangula (164.90 ± 26.24 eggs). The incubation period was shortest on S. nigrum (3.25 ± 0.97 days) and longest on Datura Stromonium (5.40 ± 0.75 days) whereas per cent egg hatchability was highest on Solanum tuberosum (91.75 ± 3.73 %) and lowest on L. acutangula (82.00 ± 5.94%). E. vigintioctopunctata grubs developed differently on eight host plants, shortest on S. nigrum (13.25 ± 1.12 days) and longest on D. stromonium (21.55 ± 1.70 days) and survived best on S. nigrum and P. minima (92.00±1.22 and 91.25±0.88%) and worst on L. acutangula (45.25±2.45%). More females than males were found among emerged adults and females lived longer than males. Pupal development was shortest on S. nigrum (3.85 ± 0.67 days) and longest in M. charantia (6.10 ± 0.72 days), wherein, adult emergence rate was highest on S. nigrum (94.25±0.98%) and lowest on L. acutangula (53.25±2.18%). Further on the basis of growth index, fecundity, survival and adult emergence, S. nigrum and P. minima were recorded to be the most suitable host plants followed by S. melongena, S. tuberosum, S. esculentum, M. charantia and D. stromonium. L. acutangula was the least preferred host plant by the test insect for overall growth and development.